2013
DOI: 10.1371/journal.pone.0058818
|View full text |Cite
|
Sign up to set email alerts
|

Eyes Absent Tyrosine Phosphatase Activity Is Not Required for Drosophila Development or Survival

Abstract: Eyes absent (Eya) is an evolutionarily conserved transcriptional coactivator and protein phosphatase that regulates multiple developmental processes throughout the metazoans. Drosophila eya is necessary for survival as well as for the formation of the adult eye. Eya contains a tyrosine phosphatase domain, and mutations altering presumptive active-site residues lead to strongly reduced activities in ectopic eye induction, in vivo genetic rescue using the Gal4-UAS system, and in vitro phosphatase assays. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 44 publications
3
30
1
Order By: Relevance
“…Recent work has shown that this catalytic function of Eya is dispensable for Drosophila development (Jin et al 2013). What then might be the role of cytoplasmic Eya?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that this catalytic function of Eya is dispensable for Drosophila development (Jin et al 2013). What then might be the role of cytoplasmic Eya?…”
Section: Discussionmentioning
confidence: 99%
“…Eya also carries two different phosphatase domains, one with specificity for phosphotyrosine and a second directed toward phosphothreonine (Li et al 2003;Rayapureddi et al 2003;Tootle et al 2003;Okabe et al 2009). Although Eya's tyrosine phosphatase is not required for normal development in Drosophila (Jin et al 2013), in mammals it dephosphorylates H2AX to promote repair and survival in response to DNA damage (Cook et al 2009;Krishnan et al 2009) and aPKCz to direct lung epithelial polarity and morphogenesis (El-Hashash et al 2012). Eya's threonine phosphatase is less well characterized, but appears to act both cytoplasmically to regulate innate immunity and nuclearly to provide transactivation and regulate the activity of other transcription factors (Okabe et al 2009;Liu et al 2012;Xu et al 2014;Jin and Mardon 2016).…”
mentioning
confidence: 99%
“…If so, then plants provide an opportunity to study the in vivo function and regulation of Eya tyrosine phosphatase activity without the complications associated with its other role as a transcription factor. The plant ED also stands out as having the strongest in vitro catalytic activity of all Eya family members tested (58) (40,55,58), perhaps plant Eya offers the best path toward unraveling the mysteries of this novel eukaryotic phosphatase. From a structural biology perspective, determination of whether the plant ED fold has intrinsic Six binding potential might provide insight into the evolutionary trajectory that separates plant from animal Eya proteins, and by extension, the physical mechanisms by which animal Eya proteins integrate their dual functions as transcription factors and protein tyrosine phosphatases.…”
Section: The Great Debate: Is Eya's Tyrosine Phosphatase Activity Dedmentioning
confidence: 99%
“…A new twist emerged in 2013 when the Drosophila Eya field was turned upside down by the demonstration that Eya's tyrosine phosphatase activity is dispensable for normal development, fertility, and survival (55). Whereas earlier studies had relied on overexpression-and misexpression-based genetic assays to show compromised output from phosphatase-dead Eya (39,40,49,56,57), Percentages of amino acid identities and similarities were calculated using LALIGN and are shown above and below the diagonal white line, respectively.…”
Section: The Great Debate: Is Eya's Tyrosine Phosphatase Activity Dedmentioning
confidence: 99%
See 1 more Smart Citation